Before Brasília - Izabel Missagia de Mattos (Revista Brasileira de História & Ciências Sociais, 2018)
Resenha do livro KARASH, Mary C. Before Brasília: Frontier Life in Central Brazil. Albuquerque: University of New Mexico Press, 2016.